Peran Lembaga Adat Tigo Luhah Semurup dalam Penyelesaian Sengketa Tanah Warisan di Semurup - Rahman, Khawarizmi; Dewi, Susi Fitria; Rafni, Al; Bakhtiar, Yusnanik (Al-DYAS, 2025)
This research aims to describe the role of the Tigo Luhah Semurup Traditional Institution in resolving inherited land disputes in Semurup, as well as revealing the supporting and inhibiting factors of the Tigo Luhah Semurup Traditional Institution in resolving inherited land disputes in Semurup. The type of research used is qualitative research with descriptive methods. Determining research informants was carried out using a purposive sampling technique, namely informants were determined by researchers to obtain the required information, namely informants who were considered to know, understand and have experience related to this research. Data collection techniques and tools are carried out by means of observation, interviews and documentation. The tools used were observation sheets, interview guides, and cameras. Testing the validity of the data uses source triangulation. Data analysis techniques are data collection, data reduction, data display and drawing conclusions.The results of the research show that the role of the Tigo Luhah Semurup traditional institution in resolving land disputes, it has been very good, this can be seen from the fact that almost all disputes resolved in traditional institutions have been successful, as for the role of the Tigo Luhah Semurup traditional institution as a mediator, facilitator and decision maker. Then there are several factors that hinder the Tigo Luhah Semurup traditional institution in carrying out its role, including; 1) Difficulty in calling/inviting disputing parties to deliberation, 2) Limited budget so that the customary justice process does not run optimally, 3) low commitment from members of traditional institutions in resolving disputes.. However, there are several supporting factors for the Tigo Luhah Semurup traditional institution in carrying out its role, including; 1) the presence of experts and intellectuals in the dispute resolution process, 2) good communication head of traditional institutions, 3) the existence of social legitimacy for the Tigo Luhah Semurup traditional institution.